The Role of Zakat in Strengthening the Resilience of Families Affected by Stunting in West Nusa Tenggara - Muhammad Dimas Hidayatullah Wildan; Dahlia Hidayati; Rahmat Saputra (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2026)
This article discusses the role of zakat in strengthening the resilience of families affected by stunting in West Nusa Tenggara Province (NTB), focusing on two districts with high stunting prevalence, namely East Lombok and Central Lombok. Using a qualitative approach with a case study design, this study explores the socio-economic conditions of mustahik families, the implementation of zakat in nutritional interventions, and opportunities for integrating zakat with regional stunting prevention policies. The results show that most families with stunted children come from poor groups with limited access to nutrition, low levels of health literacy, and unstable incomes. The implementation of zakat in NTB is currently still dominated by a charitable approach, which limits its effectiveness in strengthening families’ economic resilience. However, existing productive zakat programs have demonstrated measurable impacts, increasing family income by 25-35% and improving children's nutritional consumption patterns. The integration of zakat with regional nutrition policies has great potential to strengthen the Islamic-based social protection system. This study confirms that zakat can be a strategic instrument in addressing stunting when managed in a productive, targeted, and collaborative manner between zakat institutions and local governments.